Anti‐leukaemic activity of a novel haploidentical‐transplantation approach employing unmanipulated bone marrow followed by CD6‐depleted peripheral blood stem cells in children with refractory/relapsed acute leukaemia. (6th July 2013) - Schuster, Friedhelm R.; Meisel, Roland; Führer, Monika; Reuther, Susanne; Hauer, Julia; Tischer, Johanna; Feuchtinger, Tobias; Laws, Hans‐Jürgen; Kolb, Hans‐Jochem; Borkhardt, Arndt
Summary: The treatment outcome of children with refractory acute leukaemia or relapse post‐stem cell transplantation is dismal. We report 10 children (non‐remission n = 7) who underwent a new haploidentical transplant approach utilizing unmanipulated bone marrow followed by CD6‐depleted peripheral blood stem cells. Nine patients had successful engraftment and no evidence of leukaemia. Acute and chronic graft‐versus‐host‐disease was observed in five and three patients, respectively; two patients died of treatment‐related toxicity. Seven patients relapsed after 7 (range 3–34) months, however two patients are alive at 6·5 and 7·0 years. This approach provides anti‐leukaemic activity even in heavily pre‐treated children but long‐term disease control requires further intervention.